HUBUNGAN ANTARA PEMBERIAN KOLOSTRUM, ASI EKSKLUSIF, DAN USIA PENYAPIHAN DENGAN KEJADIAN STUNTING PADA ANAK BADUTA USIA 12-23 BULAN (ANALISIS RISKESDAS 2018) - Chindy Annisa Putri Mandala Sempaga; Sutarto; Rani Himayani (Medula, 2024)
The prevalence of stunting in Indonesia was 37.2% in 2013, 30.8% in 2018, and 27.67% in 2019. The number of stunting was indeed decreasing, but based on World Health Organization standards, the prevalence of stunting in a country is classified as high if it exceeds 20%. This shows that the prevalence of stunting in Indonesia is still high. Inadequate breastfeeding practice in the first 1.000 days of life is one of the factors that play a role in the incidence of stunting. This research is an analytic study with a cross sectional approach. The sample used comes from secondary data from Riskesdas 2018 with a total samples of 36,259. The dependent variable is the incidence of stunting and the independent variable consists of colostrum administration, exclusive breastfeeding, and weaning age. Data analysis was performed by bivariate test using chi-square. The results showed that there was a significant relationship between colostrum administration (p-value = 0.009), exclusive breastfeeding (p-value = 0.001), and weaning age (p-value = 0.001) with the incidence of stunting in children under the age of 12- 23 months. There is a significant relationship between colostrum administration, exclusive breastfeeding, and weaning age with the incidence of stunting in children under two years old aged 12-23 months. The risk factors for exclusive breastfeeding and weaning age have the same influence on the incidence of stunting in children under two years old aged 12-23 months in Indonesia.